2015
DOI: 10.1097/rli.0000000000000132
|View full text |Cite
|
Sign up to set email alerts
|

T1 Relaxivities of Gadolinium-Based Magnetic Resonance Contrast Agents in Human Whole Blood at 1.5, 3, and 7 T

Abstract: OBJECTIVES Calculation of accurate T1 relaxivity (r1) values for gadolinium-based magnetic resonance contrast agents (GBCAs) is a complex process. As such, often referenced r1 values for the GBCAs at 1.5 T, 3 T, and 7 T are based on measurements obtained in media that are not clinically relevant, derived from only a small number of concentrations, or available for only a limited number of GBCAs. This study derives the r1 values of the 8 commercially available GBCAs in human whole blood at 1.5 T, 3 T, and 7 T. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
192
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(207 citation statements)
references
References 22 publications
9
192
3
3
Order By: Relevance
“…(1.596 versus 1.541), respectively, for gadobutrol versus gadoterate, which reflect a difference in r1 relaxivity of ϳ18% based on values determined by Shen et al 5 In a comparison of gadobenate and gadobutrol, Siedl et al 4 reported differences in percentage lesion enhancement and LBR of 21.8%-24.7% and 21.4%-25.0%, respectively, which reflect a greater difference in r1 relaxivity of ϳ35%. In this study, we determined larger differences in percentage lesion enhancement and LBR of 27.6%-31.7% and 29.2%-38.1%, respectively, for equivalent doses of gadobenate and gadoterate, which reflect the still greater difference in r1 relaxivity of ϳ59%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(1.596 versus 1.541), respectively, for gadobutrol versus gadoterate, which reflect a difference in r1 relaxivity of ϳ18% based on values determined by Shen et al 5 In a comparison of gadobenate and gadobutrol, Siedl et al 4 reported differences in percentage lesion enhancement and LBR of 21.8%-24.7% and 21.4%-25.0%, respectively, which reflect a greater difference in r1 relaxivity of ϳ35%. In this study, we determined larger differences in percentage lesion enhancement and LBR of 27.6%-31.7% and 29.2%-38.1%, respectively, for equivalent doses of gadobenate and gadoterate, which reflect the still greater difference in r1 relaxivity of ϳ59%.…”
Section: Discussionmentioning
confidence: 99%
“…5 That differences in r1 relaxivity reflect differences in diagnostic efficacy is borne out by evidence from numerous large-scale intraindividual crossover studies. [1][2][3][4][8][9][10][11] These studies have shown that differences in SI enhancement and imaging performance reflect differences in r1 relaxivity and that the magnitude of the differences in SI enhancement a Comparisons based on the number of patients with both postdose T1SE images assessed and technically adequate: n ϭ 96 for reader 1, n ϭ 94 for reader 2, and n ϭ 95 for reader 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 The results of all these intra-individual crossover studies [23][24][25][26] can be ascribed to the greater r1 relaxivity of gadobenate dimeglumine compared to gadopentetate dimeglumine (6.2 L/mmols -1 vs 4.2 L/mmols -1 at 1.5 T). 21 Since r1 relaxivity is the single most important para meter defining contrast efficacy in terms of signal intensity enhancement, similar superiority for gadobenate dimeglumine can be anticipated for intra-individual comparisons of this agent with other GBCAs that have r1 relaxivity values similar to that of gadopentetate dimeglumine.…”
mentioning
confidence: 99%
“…19 The extent to which a GBCA shortens the relaxation times depends on the relaxivity of the agent. GBCAs have different structures and physicochemical properties but most have similar r1 relaxivity values of 3.9-4.6 L/mmols -1 at 1.5 T. 21 Of the GBCAs available for breast imaging gadobenate dimeglumine (MultiHance ® ; Bracco imaging, Milan, Italy) has a markedly higher r1 relaxivity in vivo of 6.2 L/mmols -1 at 1.5 T. Several studies have demonstrated an association between the use of contrast agents with higher r1 relaxivity and stronger contrast enhancement in comparison to contrast agents with lower r1 relaxivity. For most clinical applications, the stronger enhancement has been shown to be associated with a clinically relevant gain in diagnostic performance.…”
mentioning
confidence: 99%